Religion And Ethnicity as Political Power in the 2019 Dolok Manampang Village Head Election - Windawati Pinem; Prayetno Prayetno; Muhammad Iqbal (JED (Jurnal Etika Demokrasi), 2023)
This study aims to see the religious and ethnic political power used during the 2019 Dolok Manampang village head election. The problem in this study is that religion and ethnicity are often used as political tools to divide society. Still, in this election, it is used as a positive political force. After the existence of Law No. 6 of 2014, the selection of village heads is now considered a good and prestigious political battle. This made local political actors start racing for power. But to be able to get public support requires a political force. The political forces used are religion and ethnicity to influence voter behavior. The research method used is qualitative with a descriptive approach. Data collection was carried out using interviews, observations, and literature studies. Data analysis is carried out by the triangulation method. As for the results of this study, first, the candidate for village head still uses religion and ethnicity as political forces. Second, the political behavior of the people of Dolok Manampang village is still influenced by religious and clan issues.